Fungal Population Analysis of Hydrocarbons Contaminated Soil: Samples from Taq-taq Oil Field in Koya City, Kurdistan Region, Iraq - Mohammed, Srwa A.; Omar, Taha J.; Hasan, Ayad H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Petroleum is often regarded as one of the environmental hazards that pose the greatest threat to human health. After radiation, petroleum and all of its byproducts and wastes are considered to have the second-worst effect on the environment. Demonstrating fungal microbiomes that flourish on soil heavily polluted by petroleum and moderately contaminated soil samples, comparing them with uncontaminated soil samples from Taq-taq (TTOPCO) through metagenomic analysis through sequencing of the 18S-V4 region. Metagenomic analysis is conducted using high-throughput sequencing technology, targeting 18 subunit ribosomal ribonucleic acid amplicons through the Illumina-HiSeq platform. In general, an increase in fungal community richness and diversity is reported in soil contaminated with petroleum. This is determined by counting the number of operational taxonomic units, performing principal coordinate analysis, and calculating α (Chao1 and Shannon indices) and ß diversity. The composition of microbial communities is significantly altered by crude oil exposure. At the phylum level, there are considerable transitions between groups B and C for Ascomycota, Basidiomycota, Chytridiomycota, Olpidiomycota, Zoopagomycota, Cryptomycota, and Mucoromycota. In examining Group D relative to Group C, there are significant differences in Ascomycota, Basidiomycota, Chytridiomycota, Olpidiomycota, and Cryptomycota. This study is an important first step in determining and understanding the fungal population of soil extensively contaminated with crude oils of the Taq-taq/Kurdistan Region of Iraq.